Entrance to Frederick Street, Port-of-Spain, Trinidad - (:unkn) unknown (My University, 2010)
Frederick Street is a bustle of activity and the city tramcar can be seen making its way down the street.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Port of Spain; Streets--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Pedestrians--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Stores, Retail--Trinidad and Tobago; Frederick Street (Port of Spain)